Hubungan Pengetahuan Guru dengan Upaya Pencegahan tentang Cedera pada Anak Usia 6-12 Tahun di 3 SD Sumberejo - Khoirul Nadira; Ariyanti Wardiyah; Setiawati Setiawati (Malahayati Nursing Journal, 2025)
ABSTRACT The incidence of injuries in Indonesia in 2022 is 9.7%. This prevalence has increased compared to 2014, namely 7.3% and 2007, 7.9%. The prevalence of injuries at ages 1-4 years was 8.2% and at ages 5-14 years was 12.1% and the highest prevalence of injuries occurred in school children, namely 13%. Meanwhile, the prevalence of injuries in Lampung province in 2020 was 8.9% and in 2021 it increased to 9.8%. It is known that there is a relationship between teacher knowledge and efforts to prevent injuries in children aged 6-12 years at 3 Sumberejo Elementary Schools in 2024. This type of quantitative research uses a cross sectional approach. The population in this study were 91 teachers who taught at SD Negeri 2, 3 and 5 Sumberejo. A sample of 91 respondents used a total sampling technique. The data analysis used is univariate and bivariate analysis with the Chi-Square Test. The results of the research show that there is a significant relationship between teacher knowledge and efforts to prevent injuries in children aged 6-12 years at 3 Sumberejo Elementary Schools in 2024 with a p-value of 0.000. There is significant relationship between teacher knowledge and efforts to prevent injuries in children aged 6-12 years at 3 Sumberejo Elementary Schools. It’s hoped that this research can provide input for teachers to further increase their knowledge and efforts to prevent injuries to their students, especially when they are in the school environment. Keywords: Injuries, Children aged 6-12 years, Knowledge, Prevention, Teachers  ABSTRAK Insiden cedera di Indonesia pada tahun 2022 yaitu sebesar 9,7%. Prevalensi ini terjadi peningkatan jika dibandingkan dengan tahun 2014 yaitu sebesar 7,3% dan tahun 2007 sebesar 7,9%. Prevalensi cedera pada usia 1-4 tahun sebesar 8,2% dan pada usia 5-14 tahun sebesar 12,1% dan prevalensi cedera tertinggi terjadi pada anak sekolah yaitu sebesar 13%. Sedangkan prevalensi cedera di provinsi Lampung pada tahun 2020 sebesar 8,9% dan pada tahun 2021 meningkat menjadi 9,8%. Diketahui adanya hubungan pengetahuan guru dengan upaya pencegahan tentang cedera pada anak usia 6-12 tahun di 3 SDN Sumberejo Tahun 2024. Jenis penelitian kuantitatif, menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah 91 orang guru yang mengajar di SD Negeri 2, 3 dan 5 Sumberejo. Sampel 91 responden menggunakan teknik total sampling. Analisa data yang digunakan yaitu analisis univariate dan bivariate dengan Uji Chi-Square. Hasil penelitian menunjukkan bahwa ada hubungan yang signifikan antara pengetahuan guru dengan upaya pencegahan tentang cedera pada anak usia 6-12 tahun di 3 SDN Sumberejo Tahun 2024 dengan nilai p-value 0.000.  Adanya hubungan yang signifikan antara pengetahuan guru dengan upaya pencegahan tentang cedera pada anak usia 6-12 tahun di 3 SDN Sumberejo. Diharapkan penelitian ini bisa menjadi masukan bagi guru untuk lebih meningkatkan pengetahuan dan upaya pencegahan cedera pada siswa nya khususnya saat berada di lingkungan sekolah. Kata Kunci: Cedera, Anak usia 6-12 tahun, Pengetahuan, Pencegahan, Guru